Sulfonated Poly(ether ether ketone) Ion-Exchange Membrane for Membrane Capacitive Deionization Applications - Cha, Ji-Hoon; ul Haq, Oneeb; Choi, Jae-Hwan; Lee, Youn-Sik (Macromolecular research, 2018)
KCI Citation Count: 6